Humoral Immune Responses in COVID-19 Patients: A Window on the State of the Art - Siracusano, Gabriel; Pastori, Claudia; Lopalco, Lucia (Frontiers in Immunology, 2020)
The novel SARS-CoV-2 is a recently emerging virus causing a human pandemic. A great variety of symptoms is associated with COVID-19 disease, ranging from mild to severe symptoms, eventually leading to death. Specific SARS-CoV-2 RT-PCR is the standard methods to screen symptomatic people; however, asymptomatic subjects and subjects with undetectable viral load escape from the screening, contributing to viral spread. Currently, the lock down imposed by many governments is an important measure to contain the spread, as there is no specific antiviral therapy or a vaccine and the main treatments are supportive. Therefore, there is urgent need to characterize the virus and the viral-mediated responses, in order to develop specific diagnostic and therapeutic tools to prevent viral transmission and efficiently cure COVID-19 patients. Here, we review the current studies on two viral mediated-responses, specifically the cytokine storm occurring in a subset of patients and the antibody response triggered by the infection. Further studies are needed to explore both the dynamics and the mechanisms of the humoral immune response in COVID-19 patients, in order to guide future vaccine design and antibody-based therapies for the management of the disease.